Cryogenic mechanics and damage behaviors of carbon fiber reinforced polymer composites. (June 2023) - Li, Yuanchen; Meng, Jinxin; Luo, Junrong; Wang, Panding; Ma, Jia; Zhao, Zeang; Lei, Hongshuai
Graphical abstract: Highlights: In-situ cryogenic tests conducted on various composite laminates. Temperature-dependent elastic-plastic constitutive laws for resin are developed. Multiscale model developed to analyze cryogenic mechanical behavior of CFRP. Property variation and failure mechanism analyzed of composites at cryogenic temperatures. Abstract: Carbon fiber reinforced polymer (CFRP) composites, which have excellent mechanical properties, are extensively employed under extreme service conditions such as cryogenic storage tanks. In this paper, a multi-scale model was developed to investigate the cryogenic mechanical performances of CFRP composites. An elastic-plastic damage law for epoxy resin was established based on experimental results, taking into account temperature dependencies. Microscopic models and macroscopic failure criteria were formulated to describe the cryogenic mechanical behavior, and in-situ cryogenic tests were conducted on laminates. Using this multiscale framework, the effects of the cryogenic environment on the mechanical properties and failure behaviors of CFRP composites were analyzed. According to the results, the characteristics of composites at low temperatures are embrittlement transformation and delamination damage. The predicted cryogenic properties and damage behaviors matched well with the in-situ test results. This study presents an efficient method for analyzing the structural performance and designing materials for cryogenic applications.